Black hole mimickers - Pérez, Daniela (2016)
We show that a spherically symmetric gravitational collapse of a star can result in a bounce ifthe equation of state behaves with sufficient rigidity just before the formation of an event horizon.The relativistic time dilation produced by the strong gravity makes the whole process to be indistinguishable from a black hole on timescales shorter than the Hubble time for a distant observer. Wesolve the Misner-Sharp equations for stellar collapse with a suitable equation of state that reducesto a polytropic at low densities and mimicks an effective cosmological constant during the collapse,finally inverting the direction of the velocity eld of the fluid. We also present some preliminaryresults of numerical simulations of these objects. We conclude that evolving gravitational systemsmight mimick, in this way, most of the properties attributed to static black holes.